93 Nicorandil plays a protective role against pressure-overload-induced cardiac dysfunction via alleviating myocardial apoptosis and improving energy metabolism. (June 2018) - Chen, Zhangwei
Abstract : Background: As one of most important metabolic sensors, ATP-sensitive potassium channels (KATP) could regulate cellular activity to meet energetic demands. It has also been demonstrated that KATP plays a cardioprotective role on cardiac dysfunction. However, there are few studies to clarify whether KATP opener could directly improve left ventricular remodelling and heart failure caused by systolic overload. Objectives: This experimental study was designed to clarify the effect and mechanism of nicorandil (a KATP opener) on cardiac dysfunction and left ventricular remodelling in transverse aortic constriction (TAC) mice model. Methods: Mice TAC models were developed and observed at 4 weeks after operation. In nicorandil treatment group, nicorandil was injected intraperitoneally daily for 2 weeks from the third week of TAC operation. Cardiac function and left ventricular diameters were detected by echocardiography. In order to neutralise the effect of nicorandil, sarcolemmal KATP channel selective blocker (Cibenzoline, 1 mg/kg/d, abcam, No: ab145975) and mitochondrial KATP channel blocker (5-hydroxydecanoate, 10 mg/kg/d, sigma, No: 71186–53–3) were injected intraperitoneally daily 10 min before nicorandil treatment in two subgroups. Mitochondria isolated from hearts, while ATP assay (using an ATP assay kit, FLAA, Sigma, USA) and reactive oxygen species (ROS) assay (MAK143, Sigma, USA) were performed respectively. Caspase3, PGC-1, Glut-4 and five complex of oxidative phosphorylation in mictochondria were detected by Western blot. Meanwhile, myocardial apoptosis was also detected by TUNEL staining. Results: Compared with sham-operation group, TAC groups had significantly worse cardiac function (LVEF: 31.8±4.8% vs. 67.2±3.2%, p<0.01). Nicorandil treatment not only improved LVEF (LVEF: 52.3±5.8% vs. 31.8±4.8%, p<0.01), but also reduced the ratio of heart and body weight (0.63±0.06 vs. 0.81±0.14, p<0.01). Nicorandil also increased myocardial ATP synthase and reduced ROS. However, in Cibenzoline or 5-hydroxydecanoate subgroups, the protective effect of nicorandil was significantly eliminated. We also found that the average number of apoptotic cardiomyocyte nuclei and cleaved-caspase3 expression, which were improved in nicorandil group, were significantly elevated in nicorandil combined with Cibenzoline or 5-hydroxydecanoate subgroups again. Myocardial expression of PGC-1 and Glut-4 detected by Western blot was also reduced in TAC group, which was significantly increased after nicorandil treatment. Conclusions: KATP opener nicorandil protected against pressure-overload-induced cardiac dysfunction, which were associated with myocardial apoptosis improvement and energy metabolism recovery.